Neural functions of bisecting GlcNAc - Kizuka, Yasuhiko; Taniguchi, Naoyuki (Glycoconjugate journal, 2018)
Bisecting GlcNAc, a branch structure in N -glycan, has unique functions and is involved in several diseases including Alzheimer’s disease (AD). In this review, we provide an overview of the biosynthesis of bisecting GlcNAc and its physiological and pathological functions, particularly in the nervous system where bisecting GlcNAc is most highly expressed. The biosynthetic enzyme of bisecting GlcNAc is N -acetylglucosaminyltransferase-III (GnT-III). Overexpression, knockdown, and knockout of GnT-III have so far revealed various functions of bisecting GlcNAc, which are mediated by regulating the functions of key carrier proteins. GnT-III-deficient AD model mice showed reduced amyloid-β (Aβ) accumulation in the brain by suppressing the function of a key Aβ-generating enzyme, β-site APP-cleaving enzyme-1 (BACE1), and greatly improved AD pathology. Altered BACE1 subcellular localization in GnT-III-deficient cells, from early endosomes to lysosomes, suggests that bisecting GlcNAc serves as a trafficking tag for the movement of modified proteins to an endosomal compartment. For therapeutic application, we have employed high-throughput screening to search for GnT-III inhibitors. These findings highlight the importance of bisecting GlcNAc modification in the nervous system.